A new record of Tylenchus stachys Brzeski, 1996 (Nematoda:Tylenchidae) from China (Journal of Nematode Morphology and Systematics, 2010)
A population of Tylenchus stachys found around the roots of Acer sp. from China is described and compared with the original description. Description, measurements and illustrations are provided. This is the first report of T. stachys from China. The population is also compared to T. skarduensis and T. safroni, similar species with areolated lateral fields.